The Benefits of Interdisciplinary Collaboration in Community-Engaged Research: Insights From a Study of Digital Storytelling With Marginalized Youth - Carlos Jimenez; Yolanda Anyon; Lynn Schofield Clark; Heather Kennedy (The University of Alabama, 2022)
This article draws on qualitative data from a long-term partnership to exemplify the unique advantages of interdisciplinary and collaborative approaches in community-engaged research. We demonstrate how the differing foci and intersecting concerns of our scholarly fields, social work and media studies, benefited our work with marginalized communities to promote youth voice through digital storytelling. This effort was grounded in the shared view that digital storytelling offers an excellent opportunity to engage creatively with young people's memories and experiences and that such storytelling can support young people in their healing, identity formation, agency development, and engagement with the public. By working together across disciplines, we were able to surface and address concerns related to vulnerability, privacy, and advocacy among young people experiencing marginalization in ways that would not have been possible in a project involving only social work or media studies. We illustrate this process by describing three critical incidents that exposed our disciplinary overlaps and differences in ways that helped us navigate complex issues related to young people shared their stories with the public. Our findings therefore have implications for others working with vulnerable communities to amplify counternarratives with the goal of bringing about positive systemic change.